2010
DOI: 10.1111/j.1564-913x.2010.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

The Indian informal sector: The impact of globalization and reform

Abstract: Globalization and economic reforms typically affect the formal sector, the informal sector existing outside regulation. Yet, numerous links between them mean the informal sector is variously affected. Traditionally, the model used to explain the impact of these forces was labour market segmentation and migration: workers laid off in the formal sector increase informal labour supply, leading to wage decline and increased poverty. The author examines whether this pattern applies in India following economic refor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…However, others have argued that workers do not generally opt out of the formal economy by choice and that formal‐sector employers reap most of the benefit (Valodia, 2001; Altman, 2008; Valodia & Devey, 2010, all cited in Meagher, 2013, p. 8). In India, whereas some studies have suggested that such labor market linkages increased demand for informal workers without reducing their wages (Siggel, 2010), many others have argued that informal‐sector workers suffered increased poverty (Arvin‐Rad, Basu, & Willumsen, 2010, Breman, 1996, 2010, Harriss‐White & Gooptu, 2001; Marjit & Maiti, 2006; Sinha & Adam, 2006, cited in Meagher, 2013). Related literature on the global value chains also shows more evidence of intensifying poverty and vulnerability within the informal sector (Meagher, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, others have argued that workers do not generally opt out of the formal economy by choice and that formal‐sector employers reap most of the benefit (Valodia, 2001; Altman, 2008; Valodia & Devey, 2010, all cited in Meagher, 2013, p. 8). In India, whereas some studies have suggested that such labor market linkages increased demand for informal workers without reducing their wages (Siggel, 2010), many others have argued that informal‐sector workers suffered increased poverty (Arvin‐Rad, Basu, & Willumsen, 2010, Breman, 1996, 2010, Harriss‐White & Gooptu, 2001; Marjit & Maiti, 2006; Sinha & Adam, 2006, cited in Meagher, 2013). Related literature on the global value chains also shows more evidence of intensifying poverty and vulnerability within the informal sector (Meagher, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both enthusiasts and sceptics of the liberalization-induced growth indicate that poverty has either increased, remained stagnant, or on the most positive evaluation, marginally decreased in India in the postliberalization era (Patnaik, 1997 : 174-176 ;Bhaskar & Gupta, 2007 ;Jha, 2008 ;Nayyar, 2006 : 818-822). While on one hand, liberalization of the economy failed to have any visible impact on poverty reduction, liberalization-induced structural adjustments adversely impacted the livelihoods of the significant number of the working population (Harriss-White & Sinha, 2007 ;Siggel, 2010 ;Agarwala, 2013 : 3 ;Agarwala, 2008 : 382 ;Basu & Maertens, 2007 : 163). In order to compete in the newly opened up economy, businesses and industries increasingly started to move their activities from the formally regulated domain to the informal unregulated sphere (Agarwala, 2013 : 2, 40-41 ;Siggel, 2010 ;Agarwala, 2008 : 389 ;Basu & Maertens, 2007 ;Castells & Portes, 1989 : 12-15, 26-31).…”
Section: Informal Workers' Aggregation Inmentioning
confidence: 99%
“…While on one hand, liberalization of the economy failed to have any visible impact on poverty reduction, liberalization-induced structural adjustments adversely impacted the livelihoods of the significant number of the working population (Harriss-White & Sinha, 2007 ;Siggel, 2010 ;Agarwala, 2013 : 3 ;Agarwala, 2008 : 382 ;Basu & Maertens, 2007 : 163). In order to compete in the newly opened up economy, businesses and industries increasingly started to move their activities from the formally regulated domain to the informal unregulated sphere (Agarwala, 2013 : 2, 40-41 ;Siggel, 2010 ;Agarwala, 2008 : 389 ;Basu & Maertens, 2007 ;Castells & Portes, 1989 : 12-15, 26-31). In order to avoid production costs and maximize profits, businesses tended to either sub-contract their production or engage informal workers (Castells & Portes, 1989 ;Benton, 1989 ;Agarwala, 2008 : 382, 389 ;Routh, 2011).…”
Section: Informal Workers' Aggregation Inmentioning
confidence: 99%
“…In this sub-section, the theoretical studies in this area have been discussed and an attempt has been made to comprehend which hypothesis suits the case of India's unregistered sector. Siggel (2010) argues that impact of globalisation and economic reforms will be mainly felt by the registered sector because the informal sector operates in the shadow of regulations. If the registered sector is adversely affected by trade liberalisation, then the sector shrinks with a rise in unemployment.…”
Section: Association Between Trade Liberalisation and The Unregisterementioning
confidence: 99%